Amorphous Carbon Film with Self‐modified Carbon Nanoparticles Synthesized by Low Temperature Carbonization of Phenolic Resin for Simultaneous Sensing of Dopamine and Uric Acid. Issue 10 (12th August 2021) - Li, Jilong; Wang, Yanhui; Li, Rushuo; Lu, Bowen; Yuan, Yungang; Gao, Hongwei; Song, Shiwei; Zhou, Shuyu; Zang, Jianbing
Abstract: A self‐modified film electrode consisting of homogeneous snowflake‐shaped nanoparticles on the amorphous carbon substrate (HNAC) was prepared by low temperature carbonization of phenolic resin. Such a unique structure was beneficial to enhance the electroanalysis signal responds. Simultaneous detection of DA and UA was performed on the HNAC using differential pulse voltammetry (DPV) at pH 8 phosphate buffer. The well‐defined oxidation peak potential separation reached 260 mV between DA and UA. Meanwhile, the detection limit of HNAC were 0.401 μM (DA) and 2.800 μM (UA). Abstract :